The ban on phenacetin is associated with changes in the incidence trends of upper‐urinary tract cancers in Australia - Sebastien Antoni; Isabelle Soerjomataram; Suzanne Moore; Jacques Ferlay; Freddy Sitas; David P. Smith; David Forman (Elsevier, 2014)
Abstract Background: Phenacetin is an analgesic that causes renal diseases and cancers of the upper‐urinary tract (UUT). It was banned in most countries from the late 1960s. This study aimed to evaluate, for the first time, the long‐term population impact of the phenacetin ban on UUT cancer rates. Methods: We used cancer registry data from Australia, where phenacetin was widely used, to study age‐ and sex‐specific incidence trends of cancers of the renal pelvis and the ureter after the phenacetin ban (1979). Incidence rate ratios and average annual percentage change (AAPC) were calculated to quantify changes in rates over time. Results: Incidence rates of renal pelvis cancer decreased by 52% in women and 39% in men between 1983-1987 and 2003-2007. The decline in women was stronger in states where the use of phenacetin was the most widespread, e.g. New South Wales (AAPC: −4.1%; 95% CI −5.3, −2.9) and Queensland (AAPC: −3.3%; 95% CI −4.9, −1.8), and after the mid‐1990s. Incidence rates of ureteral cancer remained stable for both sexes throughout the study period. Conclusions: Our findings strongly suggest a beneficial impact of the ban on phenacetin on the incidence of renal pelvis cancer in Australia, particularly among women.